Modal intelektual dan nilai perusahaan pada industri jasa dan pertambangan di Indonesia - Herlina Rahmawati Dewi; Liska Mutiara Chandra Dewi (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2020)
Intangible assets become very important for companies in the knowledge-based business era because the value of the company is very dependent on these assets. However, not many studies about intellectual capital have measured relational capital (MVAIC method). The objectives of this study are to find out: (1) The effect of intellectual capital on company value (2) The differences in the effect of intellectual capital when it is measured using VAIC or MVAIC method on company value. The population in this study are service companies and mining companies that are consistently listed on the Stock Exchange during the period 2013-2017. Data analysis used simple linear regression analysis. The results of this study indicate that (1) There is no positive influence between intellectual capital on company value. (2) There is no difference in the effect of intellectual capital when it is measured by VAIC or MVAIC method on company value. Even though this study has not provided the expected results, the results of this study are very important for companies to give more attention in relational capital as a part of knowledge management.